The relationship between sod strength and turf quality of common grass cultivars. - Prończuk, Sławomir; Żurek, Grzegorz (Plant Breeding and Seed Science, 2008)
The sod strength, rooting depth and turf quality (expressed by shoot density and visual merit) of ten turf grass cultivars were studied during three years under medium intensive turf maintenance. Cultivars of smooth stalked meadow grass (SMG), prostrate meadow grass, tall fescue (TF), red fescue., tufted hairgrass (TH) and perennial ryegrass (PR) were examined. Simple and fast evaluation ‘hand tool’ to determine overall sod strength was used. Seasonal variation of traits for tested cultivars was described. The highest values of sod strength were noted for SMG cultivars and the lowest – for PR, TF and TH cultivars...